Assessment of mackerel stock along the Indian coast - Noble, A; Gopakumar, G; Pillai, N Gopalakrishna; Kulkarni, G M; Kurup, K Narayana; Reuben, S; Sivadas, M; Yohannan, T M (Indian Journal of Fisheries, 2011)
Study on the stock of mackerel. Ra.ftrtlligtr kmlagurta. along the west cout durin, 1984-88 revealed thatits annual averaae yield was short of only 891 tannes to the estimared MSY of SO 732 tonnes. The effort has tobe increased by another 61 % to reach t!le MSY level. AI it may be uneconomical the present level of fishing canbe taken to be at its optimwn. Similar studies on the east coast. however, showed that the exploitation hassurpassed the MSY level but the yield fell short of MSY by I 609 tannes. A 39% reduction in effort is neededto maintain the fishery at the MSY level. At the all-India level the fishery was almost at the MSY level with anaverage annual catch of73 571 tonnea against the MSY of73 521 toones. Further increase in effort would onlyreduce the catch. A reduction in effort by 21 % can yield almost the same quantity improvin, economics of thefishery and can save large-scale exploitation of young mackerel found along Andhra coast.